'Race' and community care (Buckingham : Open University Press, 1996)
'Race' and community care. 'Race', welfare and community care. Defining and containing diversity. Family obligations and social change among Asian communities. Looking after their own? Family care-giving among Asian and Afro-Caribbean communities...
Keywords: Great Britain; Social service; Minorities; Minorities -- Services for -- Great Britain; Social work with minorities -- Great Britain; Community health services -- Great Britain; Race discrimination -- Great Britain